THE EFFECT OF SOMATOTYPE ON CARDIOVASCULAR ENDURANCE IN FOOTBALL PLAYERS - -, M. Adam Mappaompo (Department of Physical Education, Sport, Health and Recreation, 2022)
This study was to determine the level of cardiovascular endurance of Bilopa FC football athletes related to somatotype. The subjects of this study were soccer athletes who were actively involved in the Bilopa FC Football Association in the city of Makassar. The population of this study amounted to 67 people, with an age range of 13-29 years. Samples were taken based on purposive sampling and selected 25 people in the age category 20-29 years. This study is a quantitative study, which aims to see the effect of somatotypes on physical fitness in soccer athletes. Somatotype data is taken based on the somatotype method that is often used the modified somatotype method introduced by Heath and Carter (2002), while the physical fitness data taken is cardiovascular endurance using the Bleep test. This study showed that the mesomorph somatotype 100% had cardiovascular endurance in the very good category. The ectomorph somatotype showed that 36.36% had cardiovascular endurance in the very good category, 54.55% in the good category, and 9.09% in the average category. The results showed that mesomorph somatotypes had better cardiovascular endurance than ectomorph somatotypes.